2011
DOI: 10.1002/pds.2176
|View full text |Cite
|
Sign up to set email alerts
|

Risk of falls associated with antihypertensive medication: self‐controlled case series

Abstract: The study provides evidence that at least some of our earlier estimates were subject to confounding. Nevertheless, thiazide prescription remains associated with an increased risk of first fall, and this effect is strongest in the first 3 weeks of prescription. Our study demonstrates that the case series method provides an effective way to assess the extent of residual confounding in case-control studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 8 publications
5
48
1
1
Order By: Relevance
“…A fall is the main etiologic factor in more than 90% of hip fractures. 15 Other designs involving a case-crossover study of inpatients 23 and an SCCS study involving elderly patients 22 have demonstrated an immediate increased risk of falls with an antihypertensive drug during the initiation of therapy. These findings support the underlying mechanism of orthostatic hypotension 22,23 and suggest that residual confounding is unlikely to be a problem in this study.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…A fall is the main etiologic factor in more than 90% of hip fractures. 15 Other designs involving a case-crossover study of inpatients 23 and an SCCS study involving elderly patients 22 have demonstrated an immediate increased risk of falls with an antihypertensive drug during the initiation of therapy. These findings support the underlying mechanism of orthostatic hypotension 22,23 and suggest that residual confounding is unlikely to be a problem in this study.…”
Section: Commentmentioning
confidence: 99%
“…17 Most studies [18][19][20][21] on the association of antihypertensive drug use and fracture risk have focused on long drug-exposure periods (at least several months) in which the underlying mechanism of action is thought to be related to bone metabolism. Studies indicate that initiation of antihypertensive drugs such as thiazide diuretics 22 and angiotensin II receptor antagonists/ blockers 23 can increase fall risk in the elderly. However, there is little information to date about the immediate increased risk of hip fracture during the initiation of antihypertensive therapy in hypertensive elderly persons.…”
mentioning
confidence: 99%
“…10,13,14,17,18 The key advantage of a self-controlled case series design is that time-invariant confounders, such as sex, location, genetics and underlying state of health, are controlled for implicitly. 14 In the conditional Poisson regression model, we adjusted only for age at the index date and development of atrial flutter or fibrillation (ICD-9-CM code 427.3), which was included as a time-varying term.…”
Section: Discussionmentioning
confidence: 99%
“…Риск падений существенно повышается в первые недели после начала лечения [43,44]. В то же время есть данные о снижении риска падений у пожилых под влиянием ингибиторов АПФ и БКК, причем более высокие дозы этих препаратов ассоциировались с большим снижением риска падений [45].…”
Section: Pharmacotherapy Of Hypertension In the Elderly фармакотерапиunclassified